A Case of Granulomatosis with Polyangiitis in Pregnancy - Rashid Naseem Khan; Aliya Naseem; Muhammad Athar Khan; Qurat ul Ain Qurat ul Ain; Mamoona Hashim; Hafiza Laila Hashim Khan (Pakistan Journal of Medicine and Dentistry)
Granulomatosis with polyangiitis, a rare autoimmune disease affecting organs such as the respiratory system, kidneys, and lungs, poses unique challenges in pregnancy. A 25-year-old woman with chronic liver disease, vasculitis, protein C and S deficiency, hypothyroidism, and gestational diabetes presented at 24 weeks gestation with shortness of breath, fever, and vomiting. Her thrombocytopenia was managed with transfusions, and regular prenatal ultrasounds were conducted. At 36 weeks, an elective cesarean delivered a healthy 2.4 kg baby. This case highlights the critical role of multidisciplinary care in achieving favorable outcomes in complex pregnancies affected by granulomatosis with polyangiitis.